Karakteristik Bio Impedence Analysis Mahasiswa Baru Fakultas Kedokteran Universitas Sriwijaya - Thaher, M. Iman Tarmizi; Putri, Catherine Dwi Augusthi; Laeto, Arwan Bin (NUTRIX, 2026)
Technological developments have led to an increase in sedentary lifestyles and unhealthy eating habits, which can affect physical fitness and potentially disrupt students' health. This study aimed to assess the bioimpedance analysis characteristics of new students at the Faculty of Medicine, Universitas Sriwijaya. The method used was a descriptive observational approach with a quantitative design, involving 74 active students from the Faculty of Medicine. Research data were collected using electronic forms and a bioimpedance analyzer, then entered into Ms. Excel and analyzed for characteristics using SPSS. The results showed that the mean body mass index, calorie requirements, visceral fat, body age, and muscle mass were higher in male students, while the average elements of total fat and subcutaneous fat were higher in female students. As many as 26.9% of male students are classified as obese, and 23.1% have high visceral fat. As many as 42.3% of female students are classified as having very high total fat. Approximately 23.1% of male students have a high muscle mass. In conclusion, male and female students show varied bioimpedance analysis characteristics due to various influencing factors. This study highlights important notes to consider in maintaining students' physical fitness to prevent degenerative diseases. Perkembangan teknologi menimbulkan peningkatan gaya hidup sedentari dan pola makan tidak sehat, yang dapat mempengaruhi kebugaran tubuh dan berpotensi mengganggu kesehatan mahasiswa. Penelitian ini bertujuan untuk menilai karakteristik Bio Impedance Analysis mahasiswa baru Fakultas Kedokteran Universitas Sriwijaya. Metode yang digunakan adalah pendekatan deskriptif observasional dengan desain kuantitatif, yang diikuti oleh mahasiswa aktif Fakultas Kedokteran sebanyak 74 mahasiswa. Data penelitian dikumpulkan menggunakan formulir elektronik dan alat Bio Impedance Analyzer, lalu data dimasukkan ke dalam aplikasi Microsoft Excel dan dianalisis karakteristiknya menggunakan SPSS. Hasil penelitian menunjukkan rerata elemen indeks massa tubuh, kebutuhan kalori, lemak viseral, usia tubuh dan massa otot lebih dominan pada mahasiswa laki-laki. Sedangkan rerata elemen lemak total dan lemak kulit lebih tinggi pada kelompok mahasiswa perempuan. Sebanyak 26,9% mahasiswa laki-laki memiliki status obesitas dan sebanyak 23,1% tergolong memiliki lemak viseral yang tinggi. Sebanyak 42,3% mahasiswa perempuan tergolong memiliki lemak total yang sangat tinggi. Sebanyak 23,1% mahasiswa laki-laki memiliki massa otot yang tergolong tinggi. Kesimpulannya, mahasiswa laki-laki dan perempuan menunjukkan karakteristik Bio Impedance Analysis yang bervariasi akibat berbagai faktor yang mempengaruhinya. Berdasarkan hasil penelitian, maka disarankan kepada mahasiswa untuk memonitor komposisi tubuh guna mencegah penyakit-penyakit degeneratif.